Political ecologies of professional practice: Plurality and possibilities in environmental governance, Introduction to the Special Section - Bimbika Sijapati Basnett; Floriane Clement; Sam Staddon (Journal of Political Ecology)
This Special Section explores the plurality of professional practice in the environment and development sector, and centers the possibilities this offers for more transformative and just futures. We bring together and foreground a uniquely (feminist) political ecology perspective on those working in environment and development, centering power and politics as a necessary component of political ecology as 'hatchet', and unpacking the often-stereotyped category 'professionals', extending solidarity and care to them as a necessary component of political ecology as 'seed.' Each of the eight articles in this Special Section offers their own version and vision of a political ecology of professional practice, articulating and evidencing a plurality of practices, perceptions and politics among the professionals they engage with. They bring to the fore the contradictory positions some professionals find themselves in, and the ways in which structural factors limit their opportunities for engaging in or promoting transformative change. They also highlight the importance of sharing ideas and practices, both in creating tensions in the workplace, but also as offering opportunities for learning and doing things differently. With regards to possibilities for more transformative and just futures, the articles may be read as both disheartening and hope-ful. Whilst the limits of individual agency are a source of despondency, it is in the coming together and collective efforts of individuals that hope emerges. The everyday 'implicit activism' of some professionals is amplified and accelerated when others learn of/from them and join with them, and when care is centered in these relationships and actions, the emotional labor is shared and thus the ultimate cause is better supported. Political ecologists have an important role to play in creating new or engaging with existing collective efforts that actively pursue more transformative and just futures.